Effects of Chlorpromazine in Rats Trained to Discriminate Between 2 and 22 Hr Food Deprivation - Dobbe, Jennifer E.; Donovan, Bryan A.; Hoida, Emily J.; Franklin, Bethany R.; Gomer, Bailey; Johnson, Amy R.; Michener, M.J.; Nelson, Courtney L.M.; Reed, Krystal A.; Van Asten, Ryan M.; Vargo, Joseph P. (My University, 2012)
Chlorpromazine, a typical antipsychotic, has been shown to have varying effects on food intake. Chlorpromazine is a dopamine antagonist that blocks several dopamine receptors (including D1 and D2). Previous research indicated chlorpromazine (5.0mg/kg) may affect food intake in two time phases. This study looked at the effects of chlorpromazine in a food-deprivation discrimination paradigm that may serve as an animal model of 'hunger'.
Color poster with text, graphs, and tables.
Keywords: Chlorpromazine--Side effects; Rats--Training; Discrimination learning; Hunger--Psychological aspects; Posters